HEALTH PROMOTION EFFECT ON ANEMIA KNOWLEDGE AMONG FEMALE STUDENTS OF UNIVERSITAS AIRLANGGA: PENGARUH PROMOSI KESEHATAN TERHADAP PENGETAHUAN ANEMIA PADA MAHASISWI UNIVERSITAS AIRLANGGA - Atika, Nur; Putri, Nuzulul Kusuma; Herawati, Nika; Ernawaty, Ernawaty (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Anemia is a common health problem among adolescent females, which can have long-term impacts on reproductive health, cognitive performance, and productivity. Low levels of knowledge are among the key factors contributing to the high prevalence of anemia in this age group. Objective: This study aimed to assess the effect of health promotion activities on improving knowledge about anemia among female students at Universitas Airlangga who reside in the women’s dormitory. Method: This study employed a pre-test and post-test design involving 47 female students selected through accidental sampling. The health promotion activity was conducted offline, followed by pre- and post-test questionnaires. Data were analyzed using the Wilcoxon Signed-Rank Test to examine differences in knowledge scores before and after the intervention. Results: There was a significant difference between pre-test and post-test knowledge scores (p = 0.000). A total of 28 respondents demonstrated an increase in scores, with an average improvement of 19.48 points. Conclusion: Health promotion through socialization activities was effective in enhancing knowledge about anemia among adolescent girls. This educational approach holds strong potential for wider implementation, particularly by involving students as peer educators to strengthen their role as agents of change in anemia prevention.